Representasi Laki-Laki dalam Novel Bekisar Merah Karya Ahmad Tohari: Analisis Wacana Kritis dan Implikasinya bagi Pembelajaran Sastra: Male Representation in Ahmad Tohari's Novel "Bekisar Merah": A Critical Discourse Analysis and Implications for Literature Learning - Jendri Mulyadi; Devi Syukri Azhari (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Discourse is not present neutrally, but rather constructed through language choices that represent certain interests, ideologies, and social realities. This also applies to literary works that function not only as imaginative products but as discursive practices that reproduce and negotiate power relations. The novel Bekisar Merah by Ahmad Tohari is a literary work that represents the social dynamics of Javanese rural society and the complexity of gender relations. Although previous studies have focused more on female characters, the male characters in this novel play a strategic role in shaping the storyline, social structure, and ideological conflict. This study aims to analyse the representation of male characters in the novel Bekisar Merah through a critical discourse analysis approach and to uncover the ideology and power relations that accompany it, while simultaneously formulating its implications for literary studies. This study employs a qualitative approach with a descriptive analysis. The data source is the novel Bekisar Merah by Ahmad Tohari, with data in the form of narrative excerpts, dialogues, and descriptions representing male characters, analysed using a critical discourse analysis framework. The study's results show that the author employs linguistic strategies, including diction, style, sentence structure, and descriptions of socio-cultural background, to construct a diverse and problematic representation of masculinity. Male characters are portrayed as both hardworking, responsible, loyal, and wise, and as reckless and ambitious. This finding confirms that masculinity in the novel Bekisar Merah is not singular but is constructed through power relations and social structures, and is relevant as a literary learning material that encourages critical reading of texts and social realities.